Application of photodynamic therapy with 5-aminolevulinic acid and fractional CO2 laser for the management of recalcitrant plantar warts - Jiaoquan Chen; Xinyi Xie; Yingxue Liu; Fengyi Chen; Yeqing Gong; Bihua Liang; Yiling Wu; Shiqi He; Yueming Li; Huilan Zhu; Shaoyin Ma (Photodiagnosis and Photodynamic Therapy)
Significance: Plantar warts, benign lesions on the soles of the feet, are caused by the human papillomavirus (HPV) infecting keratinocytes. Complete eradication of these warts is challenging, often leading to recurrences. This study evaluates the combined clinical efficacy of topical 5-aminolevulinic acid (5-ALA) photodynamic therapy (PDT) and fractional carbon dioxide (CO2) laser treatment for recalcitrant plantar warts. Approach: Data from 10 patients with recalcitrant plantar warts were analyzed. Initially, thickened hyperkeratotic tissue was removed using a super-pulsed CO2 laser. This was followed by fractional laser application, after which a 20 % 5-ALA cream was applied occlusively for 4 h. Patients then received He-Ne laser irradiation for 30 min at an energy density of 100 mW/cm², with treatments spaced 4 weeks apart. Results: The study included 10 participants aged 24 to 53 years (mean age: 33.4 ± 8.09 years). In total, 40 lesions were treated across 1 to 9 PDT sessions, with an average of 5.2 ± 2.86 sessions per patient. Complete clearance was achieved in 3 patients (30 %), 4 patients (40 %) showed an excellent response (≥80 % improvement), while 2 patients had a partial response. One patient (10 %) showed <50 % improvement. The overall clearance rate was 70 % (28 out of 40 lesions). Aside from temporary pain during the procedure and mild erythema post-treatment, one patient developed localized proliferative scarring. After a one-year follow-up, only one patient experienced recurrence. Conclusions: The combination of 5-ALA PDT and fractional CO2 laser therapy shows promise as an effective and safe alternative for treating persistent plantar warts.